Caught in Alaska - Robbins, Alaina ([Publisher not identified], 2024)
"During a summer sailing trip, she finds herself swept away by romance. Five years later - the feelings begin to bubble up again. When Mackenzie and her adventurous friends embark on a summer trip to Alaska, they envision breathtaking landscapes and unforgettable memories aboard their charming yacht, the Northern Light. As they sail through the stunning waters and explore the vibrant town of Juneau, Mackenzie's excitement for adventure is matched only by her desire for something more-a connection that has eluded her. Amid the breathtaking views and the thrill of exploration, Mackenzie finds herself drawn to Jack, the charismatic bartender who works on the yacht. With his easy smile and deep blue eyes, he embodies the spirit of adventure she craves. As their playful banter blossoms into something deeper, Mackenzie grapples with her growing feelings for Jack while navigating her ambitions and the uncertainty of a potential romance. Five years later, she looks back fondly on her summer fling. But, when a chance encounter reunites them, their feelings reappear. As Mackenzie navigates the waters of love and second chances, she discovers that sometimes, the most incredible journeys are the ones that lead us to the places we never expected to go." --Amazon.